THE POROSITY OF GAS-SATURATED RESERVOIRS ON GIS DATA - Solodkiy, E.; Karpenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of laboratory investigation of core, well logging and seam testing the saturation influence on the porosity determination of reservoir rocks from Evgeniivske oil and gas deposit was studied. As a result of the well logging interpretation and analysis of the existing geological and geophysical information an appropriate conclusions about the influence of the saturation during porosity calculation of the reservoir rocks of Evgeniivske field were made.